Was tranken die frühen Kelten?: Bedeutungen und Funktionen mediterraner Importe im früheisenzeitlichen Mitteleuropa : Internationale Konferenz, Kloster Weltenburg 28.04.-01.05.2017 - Stockhammer, Philipp; Fries-Knoblach, Janine (Bedeutungen und Funktionen mediterraner Importe im früheisenzeitlichen Mitteleuropa, 2019)
What the so-called "early Celts" used to drink has been a matter of debate amongst scientists and in the wider public for more than a century. Finds of Mediterranean imported pottery were the reason for scholars to suspect already at an early date that the "Celts" had aimed at imitating Mediterranean drinking habits. Until recently, these drinking vessels of Greek origin and Mediterranean transport amphorae were considered proof of exactly this adoption of Greek lifestyle even north of the Alps. This is the point, where our conference came into play, the basis of which is research conducted in the context of the joint research project BEFIM (www.befim.de).00We aim at connecting innovative approaches from both arts and sciences and at profitably transferring them to the archaeological evidence. To this purpose, academics from entirely different disciplines presented their research results at the conference ? whether it be on interculturality, pottery of the early Celts, scientific analyses of food residues or wine consumption also beyond the Keltiké
Keywords: Konferenzschrift -- Kloster Weltenburg -- 2017; Getränk; Latène-Zeit; Hallstattkultur; Heuneburg; Kelten; Eisenzeit; Mitteleuropa